Where Do Patients With Cirrhosis Die? A CDC WONDER Analysis From 1999 to 2020 - Areej Iftikhar; Fatima Noor Alam; Danish Ali Ashraf; Saad Hassan Qureshi; Muzamil Akhtar; Ayesha Islam Khan; Muhammad Raza; Raheel Qureshi; Raheel Ahmed (JGH Open, 2025)
ABSTRACT Background Liver Cirrhosis is a growing cause of morbidity and mortality worldwide, but significant knowledge gaps remain regarding disparities in the place of patient death. This study aims to analyze the place of death trends for cirrhosis patients in the United States from 1999 to 2020, to direct preventive and palliative care measures. Methods In this descriptive study, death certificates were examined using the Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiologic Research (CDC WONDER) database, using ICD codes K70.3, K71.7, and K74. The variables studied were the year, sex, age, race, rural–urban, census regions, and state. Percentages of deaths in each location were trended over time for interpretation. Results Between 1999 and 2020, a total of 1 090 420 deaths were attributed to cirrhosis. The majority of these fatalities occurred in inpatient medical facilities (48.75%), followed by the decedent's home (25.71%). Men consistently exhibited higher deaths in all settings, especially in medical facility—inpatient settings (31.39%), and the highest deaths were for the 55–64 age group. NH White population reported the highest mortality in all places of death, whereas the South led mortality records among census regions. The least deaths occurred in non‐core (non‐metro) areas, and state‐wise analysis revealed California to have the highest number of deaths (75 723), seconded by Texas (55 447). Conclusion Mortality due to cirrhosis increased gradually from 1999 to 2019, with a steep rise observed in 2019–2020. Men, the White race, 55–65 years age bracket, and residents of rural and Southern census regions reported the highest number of deaths from cirrhosis.